Women and Planters during American Revolution War as Narrated in Crèvecœur’s Letters from an American Farmer (1782) - Livia Traesar; Danika Rahma Irianti; Ferry Hidayat (Rubikon : Journal of Transnational American Studies, 2022)
The paper attempts to discover a historical fact of American women’s educational achievement and self-image as well as to unravel a psychological fact of American planters’ existential crisis in the historical period of Revolution War by means of information reported by Jean Hector St. John de Crèvecœur (1735-1813) in his famous Letters from an American Farmer (1782). To make the attempt successful, two literary criticisms are done by the writers of this paper, namely feminist criticism and existentialist criticism. The feminist criticism is carried out to dig up data out of the Letters and analyze it through feminist lens, while the existentialist criticism is performed to unearth signs of existential crisis experienced by the Southern planters during the Independence War of America. After scrutinizing the Letters, it is found that Southern women during the war of independence are well-educated but have a low self-image and that Southern planters suffer anguish and despair of woeful political revolution which shutter their existential equilibrium.